"(3chGO(B" (3h(B"(3ChchS(B" .. :s (3GdCgejI GdGSJQGJjLjI hGdJOGYjGJ GdEbdjejI hGdOhdjI (B/s - (3CHh ZRdI, eMeOs; (3GdcfOj, Qje eMSfs ([(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3JQjfOR ddHMhK hGdGSJTGQGJ,s, 2022)
(3JDcO gPg GdOQGSI GdHMKjI GdUGOQI Yf zeQcR JQjfOR ddHMhK hGdGSJTGQGJy Cf efWbI zGdEfOhHGSjajcy ebHdI Ydi eQMdI LOjOI ef GdJfGaS GdOhdj, MjK jJRGjO Gdbdb GdZQHj YeheG hGdCeQjcj NUhUG ef JfGej GdfahP GdUjfj, djS aj efWbJj GdeMjW GdgGOj hGdgfOj abW, hdcf aj efGWb CNQi ef GdYGde CjVG(B. (3hHjfJ GdOQGSI GdJj CJJ JMJ YfhGf (B: ((3zchGOy hzChchSy(B... (3GdCgejI GdGSJQGJjLjI hGdJOGYjGJ GdEbdjejI hGdOhdjI(B)(3, hCYOgG cdG ef GdOcJhQ eMeO CHh ZRdI , GdHGMK GdQFjSj aj GdeQcR, hGdCSJGPI Qje eMSf GdcfOj, eSGYOI HGMK Vef hMOI GdOQGSGJ GdGSJQGJjLjI aj zJQjfORy, Cf GdJMGdaGJ JHOh EMOi Cge GdCOhGJ GdJj JdLC EdjgG GdhdGjGJ GdeJMOI GdCeQjcjI dehGLgI gPG GdfahP, EP LGAJ eSGYjgG aj gPG GdEWGQ dEMjGA GdJMGda GdQHGYj zchGOy GdPj jVe Edi LGfHgG GdjGHGf hCSJQGdjG hGdgfO CjVG, hEYdGfgG Yf GdJMGda GdKdGKj zChchSy GdPj jVe Edi LGfHgG HQjWGfjG hCSJQGdjG(B. s
(3HHdjhLQGajI (B: (3UaMI (B37-40.s
Keywords: (3GdCef GdOhdjs; (3GdYdGbGJ GdNGQLjIs; (3GdCMdGa GdYScQjIs